Differentiation of Glioma Mimicking Encephalitis and Encephalitis Using Multiparametric MR-Based Deep Learning - Wu, Wenli; Li, Jiewen; Ye, Junyong; Wang, Qi; Zhang, Wentao; Xu, Shengsheng (Frontiers in Oncology, 2021)
Background: Computational aid for diagnosis based on convolutional neural network (CNN) is promising to improve clinical diagnostic performance. Therefore, we applied pretrained CNN models in multiparametric magnetic resonance (MR) images to classify glioma mimicking encephalitis and encephalitis. Methods: A dataset containing 3064 MRI brain images from 164 patients with a final diagnosis of glioma (n=56) and encephalitis (n=108) patients and divided into training and testing sets. We applied three MRI modalities [fluid attenuated inversion recovery (FLAIR), contrast enhanced-T1 weighted imaging (CE-T1WI) and T2 weighted imaging (T2WI) ] as the input data to build three pretrained deep CNN models (Alexnet, ResNet-50 and Inception-v3), and then compared their classification performnce with radiologists’ diagnostic performance. These models were evaluated by using the area under the receiver operator characteristic curve (AUC) of a 5-fold cross-validation and the accuracy, sensitivity, specificity were analyzed. Results: The three pretrained CNN models all had AUC values over 0.9 with excellent performance. The highest classification accuracy of 97.57% was achieved by the Inception-v3 model based on the T2WI data. In addition, Inception-v3 performed statistically significantly better than the Alexnet architecture (p<0.05). For Inception-v3 and ResNet-50 models, CE-T1WI offered the highest AUC, followed by T2WI.The performance of Inception-v3 and ResNet-50 had a significant difference with radiologists (p<0.05), but there was no significant difference between the results of the Alexnet and those of a more experienced radiologist (p >0.05). Conclusions:The pretrained CNN models can automatically and accurately classify these two diseases and further help to improving clinical diagnostic performance.